Acute heart failure: vasoactive agents – does it matter? - Macas, A.; Zinkevičiūtė-Žarskienė, G. (Acta medica Lituanica, 2012)
Acute heart failure (AHF) is defined as the rapid onset of symptoms se condary to abnormal cardiac function. It is a syndrome and has a va riety of potential etiologies. AHF is a very polymorphic conception and can be related with abnormalities in cardiac rhythm, systolic or diastolic dysfunction or preload and afterload mismatch. The cornerstone of ma nagement includes therapy directed towards the underlying cause of heart failure. On the other hand, if the underlying cause is irreversible  –  a heart assist device or even heart transplantation may be needed. Therefore, while awaiting their availability, vital organ perfusion remains crucial. In these settings, intravenous cardio-/vaso- active agents are necessary. With few exceptions, most vasopressor and positive inotropic agents are symphatomimetic amines that exert their action by binding and sti mulating adrenergic receptors. They are powerful drugs with a considerable potential for toxicity. Vasopressor and inotropic support in case of AHF helps to win the time until a more definitive treatment becomes available. Therefore, AHF management must be directed to establish and eliminate deteriorational factors, however, not the correction of particular hemodynamic parameters.
Keywords: acute heart failure (AHF); vasopressors; inotropes; cardiogenic shock